Model-centered learning pathways to mathematical understanding using GeoGebra - Bu, Lingguo; Schoen, Robert C. (Robert Clarence) 1975-; SpringerLink (Online service). (Rotterdam SensePublishers, 2011)
Model-Centered Learning: Pathways to Mathematical Understanding Using GeoGebra is the first book to report on the international use of GeoGebra and its growing impact on mathematics teaching and learning. Supported by new developments in model-centered learning and instruction, the chapters in this book move beyond the traditional views of mathematics and mathematics teaching, providing theoretical perspectives and examples of practice for enhancing students' mathematical understanding through mathematical and didactical modeling. Designed specifically for teaching mathematics, GeoGebra integrates dynamic multiple representations in a conceptually rich learning environment that supports the exploration, construction, and evaluation of mathematical models and simulations. The open source nature of GeoGebra has led to a growing international community of mathematicians, teacher educators, and classroom teachers who seek to tackle the challenges and complexity of mathematics education through a grassroots initiative using instructional innovations. The chapters cover six themes: 1) the history, philosophy, and theory behind GeoGebra, 2) dynamic models and simulations, 3) problem solving and attitude change, 4) GeoGebra as a cognitive and didactical tool, 5) curricular challenges and initiatives, 6) equity and sustainability in technology use. This book should be of interest to mathematics educators, mathematicians, and graduate students in STEM education and instructional technologies
GeoGebra for Model-Centered Learning in Mathematics: An Introduction 1 The Strength of the Community: How GeoGebra can Inspire Technology Integration in Mathematics Markus Hohenwarter and Zsolt Lavicza 2 Toward Model-Centered Mathematics Learning and Instruction Using GeoGebra: A Theoretical Framework for Learning Mathematics with Understanding Lingguo Bu, J. Michael Spector, and Erhan Selcuk Haciomeroglu 3 Using Dynamic Geometry to Bring the Real World into the Classroom Robyn Pierce and Kaye Stacey 4 GeoGebra: From Simulation to Formalization in Teacher Preparation and Inservice Programs Maurice Burke and Paul Kennedy 5 Building Simulators with GeoGebra Dani Novak, Linda Fahlberg-Stojanovska, and Anthony Di Renzo 6 Influence of GeoGebra on Problem Solving Strategies Núria Iranzo and Josep Maria Fortuny 7 GeoGebra as a Conceptual Tool for Modeling Real World Problems Nicholas G. Mousoulides 8 Modeling the Cube Using GeoGebra José Manuel Arranz, Rafael Losada, José Antonio Mora, Tomas Recio, and Manuel Sada 9 Visualization Through Dynamic GeoGebra Illustrations Erhan Selcuk Haciomeroglu 10 Mathematics Attitudes in Computerized Environments: A Proposal Using GeoGebra Inés Mª Gómez-Chacón 11 GeoGebra as a Cognitive Tool: Where Cognitive Theories and Technology Meet Zekeriya Karadag and Douglas McDougal 12 GeoGebra as a Methodological Resource: Guiding Teachers to Use GeoGebra for the Construction of Mathematical Knowledge Eleonora Faggiano and Palmira Ronchi 13 Approaches to Calculus Using GeoGebra Chris Little 14 Rebirth of Euclidean Geometry? Thomas Lingefjärd 15 The Emerging Role of GeoGebra in the Philippines Ma. Louise Antonette N. De las Peñas and Debbie Bautista 16 GeoGebra, Democratic Access, and Sustainability: Realizing the 21st-Century Potential of Dynamic Mathematics for All Daniel Jarvis, Markus Hohenwarter, and Zsolt Lavicza Reflections and Conclusions Lingguo Bu and Yazan Alghazo
Includes bibliographical references
Electronic reproduction
Keywords: GeoGebra; Geometry -- Study and teaching (Secondary); Geometry -- Study and teaching (Secondary) -- Software